2021
DOI: 10.3389/fimmu.2021.669893
|View full text |Cite
|
Sign up to set email alerts
|

Premature Senescence and Increased Oxidative Stress in the Thymus of Down Syndrome Patients

Abstract: Down syndrome (DS) patients prematurely show clinical manifestations usually associated with aging. Their immune system declines earlier than healthy individuals, leading to increased susceptibility to infections and higher incidence of autoimmune phenomena. Clinical features of accelerated aging indicate that trisomy 21 increases the biological age of tissues. Based on previous studies suggesting immune senescence in DS, we hypothesized that induction of cellular senescence may contribute to early thymic invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
3
7
0
2
Order By: Relevance
“…(Note that if just two disomic and two trisomic clones were compared, results would depend on which cell lines/experiments were compared.) Our own observations comparing normal and DS human fibroblast lines suggested that trisomic cells were more susceptible to replicative senescence (Swanson,2014) (Dissertation Chapter IV), consistent with other recent evidence that trisomy 21 can increase cell senescence under stress (Oromendia et al,2012;Marcovecchio et al,2021). However, while senescence was not directly studied in this stem-cell based study, we did not detect increased expression of p16 or p21, markers of senescent cells.…”
Section: Expanded Experimental Design To Discriminate Differences Due...supporting
confidence: 90%
“…(Note that if just two disomic and two trisomic clones were compared, results would depend on which cell lines/experiments were compared.) Our own observations comparing normal and DS human fibroblast lines suggested that trisomic cells were more susceptible to replicative senescence (Swanson,2014) (Dissertation Chapter IV), consistent with other recent evidence that trisomy 21 can increase cell senescence under stress (Oromendia et al,2012;Marcovecchio et al,2021). However, while senescence was not directly studied in this stem-cell based study, we did not detect increased expression of p16 or p21, markers of senescent cells.…”
Section: Expanded Experimental Design To Discriminate Differences Due...supporting
confidence: 90%
“…T-cell exhaustion and senescence appear to be related phenomena as shown by increased CD57 expression of T-cells in DS. Recently it has been shown that premature senescence in DS thymocytes plays a key role in the pathogenesis of immune defect in DS in the context of increased oxidative stress and epigenetic regulation ( 33 ). Accelerated aging in DS thymocytes has likely contributed to the T-cell exhaustion and senescence we observed in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The common features of these pathological conditions are mitochondrial dysfunction with energy metabolism imbalance and the presence of sustained oxidative/nitrosative stress. This implies that changes in the serum levels of purines, lactate, antioxidants and nitric oxide metabolites (nitrate + nitrate) reflect the alterations of numerous biochemical functions in DS patients, potentially contributing to their accelerated aging processes [ 67 ] and to the associated decline in their neurocognitive functions [ 68 ]. It is significant to observe that the ROC curves, calculated for purines (hypoxanthine, xanthine, uric acid, sum of oxypurines and inosine), lactate, and nitric oxide metabolites (nitrate and nitrate + nitrate) have high specificity and sensitivity to discriminate PnonDSP from PDSP, whilst only the ROC curve of xanthine allows the discrimination of YDSP from ADSP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported anomalies of various amino acids in the serum samples of DS patients, compared to those that were measured in non-DS patients [ 19 , 38 , 39 , 40 ]. Again, in none of these studies was the accelerated aging process characterizing DS patients considered [ 47 , 48 , 67 ], so that the comparisons were performed between groups of non-DS and DS patients that were matched for sex and, most importantly, age.…”
Section: Discussionmentioning
confidence: 99%